The Urgency of Global Halal Standards on Products in Supporting International Trade - Sakti, Muthia (Law Research Review Quarterly, 2023)
This research endeavors to assess the imperative need for global halal standards in product certification within the regulatory frameworks of diverse countries. Employing normative juridical research methods alongside statutory, comparative, and conceptual approaches, the study seeks a comprehensive understanding of the existing landscape. The findings underscore significant disparities among halal certification bodies across various countries, attributable to variations in regulations, diverse schools of thought, cultural influences, and nuanced considerations of maslahah (public interest). These divergences necessitate urgent attention and intervention. It becomes apparent that the Standards and Metrology Institute for the Islamic Countries (SMIIC) holds a pivotal role in harmonizing global halal standards. Such harmonization is critical not only to safeguard the interests of Muslim consumers on a global scale but also to mitigate potential international trade disputes arising from the export and import of halal products. This research underscores the pressing need for concerted efforts to establish unified global standards, ensuring the integrity of halal certification processes and fostering a more transparent and equitable global trade environment for halal products. The study contributes to the ongoing discourse on harmonization and standardization within the halal industry, emphasizing the potential for enhanced consumer protection and international trade facilitation.